How to address attention deficit hyperactivity disorder (ADHD) children in private elementary school - Palacios Abarca, Rudy Baldemar,; Archila Chacón, Ana Maritza,; Alvarado Ayala, Marta Cecilia,; Paz Martínez, Mayra Aleyda,; Concepción Lino, Edson Oraldo,; Salazar Murcia, Pedro Antonio (Universidad de El Salvador, 2004)
At the University of El Salvador in the Foreign Language Department (FLD), future teachers of English are prepared to carry out formal instruction in a traditional way because the mission of the FLD states that professionals are prepared to teach at mid and superior level education when they major in English from the “Licenciatura en Inglés” program. However, when future teachers of English face real life situations when teaching children in the classroom, which is the only available market for them, they deal with different types of students’ behaviors, learning disabilities, specially Attention Deficit – Hyperactivity Disorder (ADHD) children and so on; so they are not taught how to address children who fall into this category due to several factors: The “Licenciatura en Inglés” Didactics syllabus does not include a content which at least trains the future teachers of English on how to address ADHD children. Moreover, the staff of teachers in charge of the Didactics syllabus does not plan in order to modify this curriculum to fit the unique characteristics of the English students as future teachers at the time they have to take into account children’s needs and abilities like: readiness, independence, attention span, disabilities and self-control when planning and delivering instruction. What they do is to teach contents required in the Didactics syllabus, contents they are comfortable working with since they are not specialised in delivering instruction to teach children. Finally, Didactics teachers that are in charge of the curriculum design have not done a research about what the real students needs are. Consequently, future teachers of English do not have a sense of command and personal ownership over the teaching act to ADHD children.